Media and Body Image: What’s the Connection? - Raed Nafea Farhan (Journal of Social Science and Humanities, 2025)
The development of information technology, particularly the internet and social media, has brought about significant changes in how individuals, especially teenagers and young adults, shape their perceptions of their body image. Body image disturbances often arise as negative perceptions, typically triggered by exposure to social media that showcases ideal beauty standards, such as slim or muscular bodies. Social media has become one of the main sources of social comparison, where individuals compare themselves to body images curated visually by public figures, celebrities, or peers. A qualitative approach was used, with data collection methods including the analysis of relevant academic literature, including previous research, scientific journals, and current literature. Studies show that these comparisons contribute to body dissatisfaction, particularly among adolescent girls who are vulnerable to social pressure. Surveys by APJII and We Are Social indicate that the majority of internet users are teenagers who spend hours on platforms like Instagram and TikTok. This research aims to analyse how social media influences body image perceptions among teenagers, identify the most influential factors, and explore mechanisms to help reduce the negative impact of social media on mental health and body image.